Oestrogen receptor β expression and depth of myometrial invasion in human endometrial cancer - Takama, F (Nature Publishing Group, 2001)
We assessed the relative expression of oestrogen receptor (ER)α and oestrogen receptor (ER)β mRNAs in 36 human endometrial cancers using a multiplex polymerase chain reaction (PCR). To determine whether or not the expression of ER subtypes in endometrial cancers is associated with clinicopathological parameters, we examined correlations between ER subtypes and age, tumour grade and depth of myometrial invasion. Using multiple regression analysis, myometrial invasion showed a significant correlation with ER-β: ER-α ratio (r = 0.54, P = 0.0007). The ER-β:ER-α ratio was high in advanced invasive carcinoma. Western blotting analysis showed that ER-β proteins were highly expressed in comparison with ER-α proteins in endometrial cancer with severe myometrial invasion. Our results suggest that ER-β is important in the progression of myometrial invasion. © 2001 Cancer Research Campaign http://www.bjcancer.com